ISLAMIC LAW APPROACHES IN THE IMPLEMENTATION OF REHABILITATION AS A EFFORTS TO TREAT ABUSE NARCOTICS FOR NARCOTICS IN BANDA ACEH HIJRAH FOUNDATION FOUNDATION - Sunardi Sunardi; Mustamam Mustamam; Adil Akhyar (LPPM YPITI, 2021)
Social rehabilitation through a religious approach is an effort to recover from narcotics abusers so that they can live better and be more responsible in the future. Social rehabilitation is a manifestation of the development of the Indonesian people as a whole which aims to shape the nation's character. The problems in this study, namely: What is the legal provisions for the implementation of rehabilitation for drug addicts who undergo rehabilitation? What is the provision of the rehabilitation process for narcotics addicts and how is the Islamic legal approach in implementing rehabilitation for narcotics addicts in the rehabilitation center of the Banda Aceh hijrah gate? This type of research is empirical juridical research. The data analysis used in this study is qualitative data analysis. Based on research results, the implementation of rehabilitation for narcotics addicts undergoing rehabilitation according to the Narcotics Act can be done in two ways, namely based on a court decision or recommendation from an agency with an assessment and voluntarily by carrying out compulsory reporting for themselves by an addict who is sufficient age and by parents/guardians for addicts who are not old enough. The rehabilitation process for narcotics addicts undergoing rehabilitation at the rehabilitation center of the Pintu Hijrah Banda Aceh Foundation is carried out in three stages, first, the medical rehabilitation stage (detoxification), the non-medical rehabilitation stage by following various programs in the rehabilitation place and the advanced care stage (after care) . The Islamic legal approach in the implementation of rehabilitation for narcotics addicts in the rehabilitation center of the Pintu Hijrah Foundation in Banda Aceh has a great influence on the change in behavior of narcotics residents. Based on the results of the Ministry of Social Republic of Indonesia's assessment, the percentage of successful rehabilitation of addicts is 80% of the total number of residents who have participated in rehabilitation programs at the Banda Aceh Hijrah Door Foundation.